UNDERSTANDING TOURISTS’ PERCEPTIONS OF BALI DURING POST-PANDEMIC ERA (Jurnal Sosial Humaniora dan Pendidikan, 2022)
This study investigates the effect of tourist perceptions on the post-pandemic era towards Bali tourist destination. The study results provide a basis of how COVID-19 affects tourists’ decision-making process that influenced by their travel behaviour, motivation, preferences and their experiences. Based on the results, the government policies of health protocols implementations and the power of social media influence the tourist perceptions of Bali during the post-pandemic era. The method of this study using focus group discussion with ten participants and supported by secondary data collected by the researcher. These findings contributed to the proposed strategies that increased the number of local and international tourists